ENHANCING WASTEWATER TREATMENT EFFICIENCY USING MICROBIAL FUEL CELLS: A STUDY ON DOMESTIC AND HOSPITAL SEWAGE (European Science Methodical Journal, 2025)
This study evaluates the efficiency of microbial fuel cells in treating domestic and hospital wastewater, focusing on pollutant removal, bioelectricity production, and microbial communities.